Chứng minh đẳng thức
\(\sqrt{6+\sqrt{24}+\sqrt{12}+\sqrt{8}}=\sqrt{3}+\sqrt{2}+1\)
chứng minh đẳng thức
\(\sqrt{6+\sqrt{24}+\sqrt{12+\sqrt{8}}=\sqrt{3}+\sqrt{2}+1}\)
Chứng minh các hằng đẳng thức sau:
a) \(y\sqrt{10+\sqrt{60}-\sqrt{24}-\sqrt{40}}=\sqrt{3}+\sqrt{5}-\sqrt{2}\)
b) \(\sqrt{6+\sqrt{24+\sqrt{12}+\sqrt{8}}}-\sqrt{3}=\sqrt{2}+1\)
Chứng minh các hằng đẳng thức:
a) \(\sqrt{10+\sqrt{60}-\sqrt{24}-\sqrt{40}}=\sqrt{3}+\sqrt{5}-\sqrt{2}\)
b) \(\sqrt{6+\sqrt{24}+\sqrt{12}+\sqrt{8}}-\sqrt{3}=\sqrt{2}+1\)
Chứng minh đẳng thức:
\(\left(\sqrt{12}-6\sqrt{3}+\sqrt{24}\right)\sqrt{6}-\left(4\sqrt{\frac{1}{2}}+12\right)=-14\sqrt{2}\)
\(\sqrt{17-12\sqrt{2}}-\sqrt{24-8\sqrt{8}}\)
\(\sqrt{17-3\sqrt{32}}+\sqrt{17+3\sqrt{32}}\)
\(\sqrt{11+6\sqrt{2}}-\sqrt{11-6\sqrt{2}}\)
cần gấp
Bài 1: Chứng minh:
a) \(\sqrt{9+\sqrt{17}}-\sqrt{9-\sqrt{17}}-\sqrt{2}=0\)
b) \(\sqrt{4+\sqrt{10+2\sqrt{5}}}+\sqrt{4-\sqrt{10+2\sqrt{5}}}=\sqrt{5}+1\)
c) \(\sqrt{2}+\sqrt{6}+\sqrt{12}+\sqrt{20}+\sqrt{30}+\sqrt{42}< 24\)
d) \(\sqrt{6+\sqrt{6+\sqrt{6+,,,+\sqrt{6}}}}=3\)
Tính
\(\sqrt{6+\sqrt{8}+\sqrt{12}+\sqrt{24}}\)
\(\frac{\sqrt{3}}{\sqrt{\sqrt{6}+1}-1}-\frac{\sqrt{3}}{\sqrt{\sqrt{6}+1}+1}\)
\(\sqrt{1-\frac{\sqrt{2}+1}{3}}:\sqrt{\frac{\sqrt{2}-1}{3}}+1\)
Chứng minh rằng : \(\sqrt{2}+\sqrt{6}+\sqrt{12}+\sqrt{20}+\sqrt{30}+\sqrt{42}< 24\)